Oedipus Sang Raja dan Bujang Munang: Mitos Peletak Dasar Larangan Incest dalam Masyarakat - Laura Andri Retno Martini (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Folklore is a story of the past that characterizes every nation with its diverse cultures, including the rich culture and history of each nation. The folklore that tells incest is found all over the world. In almost all ethnic groups there is an incest first mythology. Versions are submitted vary, depending on the social life of the community. Bujang Munang and Oedipus are cultural myth stories that have the theme of the origin of the incest ban. Oedipus is a myth that developed in Greece while Bujang Munang is a myth that developed in Nanga Serawai Santang district of West Kalimantan. There is a linkage of the basic structure of the narrative in the story of Oedipus and Bujang Munang. Incest behavior is also not allowed to occur in the norms of life of Greek society and the people of West Kalimantan. There will be unfavorable consequences for incest and surrounding people if the rule is violated.